Carsten Borchgrevink and the Southern Cross Expedition, 1898-1900 - Riffenburgh, Beau; Kløver, Geir O (Red.) (The Fram Museum, 2017)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; biografier; botanikk; ekspedisjonen; ekspedisjoner; forskning; første landgang; geografi; geologi; oppdagelsesreiser; overvintring; polarekspedisjoner; zoologi

Women, whales and Antarctica - Blackadder, Jesse (Whaling and History IV : papers presented at a symposium in Sandefjord on the 20th and 21st of June 2013, 2013)
Keywords: Antarktis; første landgang; historie; kvinner; oppdagelsesreiser

The first men on the last continent – Carsten Egeberg Borchgrevink and the Southern Cross expedition, 1898 -1900 - Smelror, Morten (Fram forum, 2013)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Kapp Adare; Southern Cross; Victoria Land; ekspedisjonen; ekspedisjoner; første landgang; geologi; oppdagelsesreiser; overvintring

Henrik Bull, the Antarctic Exploration Committee and the first confirmed landing on the Antarctic continent - McConville, Andrew (Polar Record, 2007)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; D/S Antarctic; Henrik Johan Bull; Kapp Adare; Leonard Kristensen; Rosshavet; Victoria Land; ekspedisjoner; forskning; første landgang; oppdagelsesreiser

Klarius Mikkelsen's landing site: some further notes on the 1935 Norwegian visit to the Vestfold Hills, East Antarctica - Norman, Frederick Ian; Gibson, John A E; Jones, R T; Burgess, J S (Polar Record, 2002)
Further details regarding the landing made by Klarius Mikkelsen in the Tryne Islands, Vestfold Hills, East Antarctica, are given, being derived mainly from newspaper accounts made by Leif Sørsdal. All involved in the landing on 20 February 1935 have been identified, details of material left in the depot under the raised flag are given, and more extended information relating to the voyage to and from the site and the area generally are presented. Some comparison is made between Sørsdal's accounts and others. While the national importance of the landing was commented on, only Sørsdal apparently realised (but did not state) the insular nature of the site. Recent observations at the site suggest that its location is 68°22′38.22″S, 78°24′50.10″E, rather than that previously stated; bracing of the flagpole itself has been modified at some stage since its erection. Finally, some discussion is made regarding on-going questions relating to the accepted time on board ship, and possible consequences of errors.
Keywords: Antarktis; Nordmenn; Thorshavn ekspedisjon; første landgang; kvinner; oppdagelsesreiser

Klarius Mikkelsen's 1935 landing in the Vestfold Hills, East Antarctica: some fiction and some facts - Norman, Frederick Ian; Gibson, John A E; Burgess, J S (Polar Record, 1998)
Exploratory activities of Norwegians, particularly those directed by Lars Christensen, off eastern Antarctica are discussed briefly in relation to contemporary Antarctic investigations and politics. The interests of Norway there and Christensen's role in establishing an understanding of the local coastline are indicated. Particular attention is paid to the landing made by Klarius Mikkelsen in the Vestfold Hills, East Antarctica, on 20 February 1935. Note is taken of the site's recent re-discovery, and the symbolic role of the landing in the national aspirations of Norway, Britain, and Australia is discussed. Mikkelsen operated under commercial and scientific interests promoted by Christensen, and his landing was, at least in published material, seen as an extension of them. However, there is a suggestion that not only had a new Norwegian land been discovered, and a landing made, but that a claim to it was at least considered. Such a claim was not appropriate given previous agreements between Norway and Britain. The site's location and environs are discussed, as are subsequent flights over it and visits made there by Australian expeditioners. The ambiguity associated with claims that Caroline Mikkelsen was the first woman to land on the Antarctic mainland is also examined. Since Mikkelsen's site was on an island within the Tryne Group, to the north of Davis station, if a mainland location is required to establish such an event, then an alternative (Scullin Monolith) is proposed; however, on this occasion four women were involved, but who was first ashore remains uncertain.
Keywords: Antarktis; Nordmenn; Thorshavn ekspedisjon; første landgang; kvinner; oppdagelsesreiser

Ashore on the continent - Quartermain, L B (South to the Pole : the early history of the Ross Sea sector, Antarctica, 1967)
Keywords: Antarctic (skip); Antarktis; Carsten Egeberg Borchgrevink; Henrik Johan Bull; Rosshavet; første landgang; oppdagelsesreiser; polarekspedisjoner

Samer i polarforskningen - Nissen, Kristian (Sameliv : Samisk selskaps årbok, 1963)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; ekspedisjonen; ekspedisjoner; forskning; første landgang; oppdagelsesreiser; overvintring; polarekspedisjoner; samer

U južnogo poljusa god 1900 - Borchgrevink, Carsten Egeberg (1958)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; biografier; botanikk; ekspedisjonen; ekspedisjoner; forskning; første landgang; geografi; geologi; oppdagelsesreiser; overvintring; polarekspedisjoner; zoologi

Das Festland am Sydpol : die Expedititon zum Sydpolarland in den Jahren 1898-1900 - Borchgrevink, Carsten Egeberg (Schottlaender, 1905)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; biografier; botanikk; ekspedisjonen; ekspedisjoner; forskning; første landgang; geografi; geologi; oppdagelsesreiser; overvintring; polarekspedisjoner; zoologi

Nærmest Sydpolen : Aaret 1900 - Borchgrevink, Carsten Egeberg (Gyldendal, 1905)
Keywords: Antarktis; Carsten Borchgrevink; Kapp Adare; Southern Cross; Sydpolen; biografier; botanikk; ekspedisjonen; ekspedisjoner; forskning; første landgang; geografi; geologi; oppdagelsesreiser; overvintring; polarekspedisjoner; zoologi

The "Southern Cross" Antarctic expedition - Newnes, George (The Strand Magazine, 1899)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Southern Cross; ekspedisjonen; ekspedisjoner; første landgang; oppdagelsesreiser; overvintring

The First Landing On The Antarctic Continent : being An Account of the Recent Voyage Of The Whaler "Antarctic" - Borchgrevink, Carsten Egeberg (The Century illustrated monthly magazine, 1896)
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Rosshavet; Victoria Land; botanikk; ekspedisjoner; forskning; første landgang; geologi; hvalfangere; hvalfangst; oppdagelsesreiser; selfangst; zoologi

The Voyage of the "Antarctic" to Victoria Land - Borchgrevink, Carsten Egeberg (Report of the Sixth International Geographical Congress. Held in London, 1895, 1896)
Keywords: Antarctic (skip); Antarktis; Kapp Adare; Rosshavet; Victoria Land; botanikk; ekspedisjoner; forskning; første landgang; geologi; hvalfangere; hvalfangst; oppdagelsesreiser; selfangst; zoologi

Den sidste antarctiske reise og foreløbig plan for en ny expedition. Foredrag den 30te oktober 1895 - Borchgrevink, Carsten Egeberg; Bull, Henrik Johan (Det Norske geografiske selskabs aarbok, 1896)
Keywords: Antarktis; Kapp Adare; forskning; første landgang; oppdagelsesreiser; overvintring; polarekspedisjoner

The Cruise of the "Antarctic" to the South Polar regions - Bull, Henrik Johan (Edward Arnold, 1896)
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Rosshavet; Victoria Land; ekspedisjoner; forskning; første landgang; geografi; hvalfangere; hvalfangst; oppdagelsesreiser; selfangst

Journal of the Right-Whaling Cruise of the Norwegian Steamship "Antarctic", in South Polar Seas under the Command of Captain Leonard Kristensen during the Years 1894-95 - Kristensen, Leonard (Transactions of the Royal Geographical Society of Australasia, Victorian Branch, 1896)
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Rosshavet; Victoria Land; ekspedisjoner; første landgang; geografi; oppdagelsesreiser

Brief Survey of Antarctic Exploration - Potter, William (Transactions of the Royal Geographical Society of Australasia, Victorian Branch, 1896)
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Leonard Kristensen; Rosshavet; Victoria Land; ekspedisjoner; første landgang; geografi; oppdagelsesreiser

A Voyage to the Antarctic Sea - Borchgrevink, Carsten Egeberg (Report of the Sixty-Fifth meeting of the British Association for the Advancement of Science helt at Ipswich in September 1895, 1895)
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Rosshavet; Victoria Land; botanikk; ekspedisjoner; forskning; første landgang; geologi; hvalfangere; hvalfangst; oppdagelsesreiser; selfangst; zoologi

The "Antarctic's" Voyage to the Antarctic - Borchgrevink, Carsten Egeberg (The Geographical Journal, 1895)
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Rosshavet; Victoria Land; botanikk; ekspedisjoner; forskning; første landgang; geologi; hvalfangere; hvalfangst; oppdagelsesreiser; selfangst; zoologi

The Voyage of the “Antarctic” to Victoria Land - Borchgrevink, Carsten Egeberg (Nature, 1895)
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Rosshavet; Victoria Land; botanikk; ekspedisjoner; forskning; første landgang; geologi; hvalfangere; hvalfangst; oppdagelsesreiser; selfangst; zoologi

Antarctics reise til Sydishavet, eller Nordmændenes landing paa Syd Victoria land - Kristensen, Leonard (Forfatterens forlag, 1895)
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Rosshavet; Victoria Land; ekspedisjoner; første landgang; geografi; oppdagelsesreiser